Groundwater Depletion and Agricultural Land Use Change in Wichita County, Kansas - Kettle, Nathan; Harrington, Lisa M.B.; Harrington, John A., Jr. (My University, 2007)
Though researchers have documented groundwater and land use changes in the High Plains, few studies have investigated their interactions. This paper examines the relationship between groundwater depletion and agricultural land use change in greater detail than previous studies. Water well measurements and satellite imagery were used to detect changes in groundwater and land cover in Wichita County, Kansas, between 1975 and 2001. Analysis of these changes using GIS indicated that areas experiencing the greatest decline in groundwater were indeed being removed from irrigation, while areas with limited groundwater decline were experiencing fewer land use changes.
Keywords: High Plains; Groundwater; Land use; Remote sensing; Kriging